Utilizando o eye-tracking para caracterizar os caminhos de leitura em textos multimodais de física - Esdras Garcia Alves (2020)
In this work we investigate how people read a multimodal text, taken from a university level Physics textbook. More precisely, we seek to evaluate the reading paths followed by readers in interaction with this text. The Physics textbook is an important resource used by teachers and students, in and out of the classroom. Reading this texts demands to integrate different modes information because its pages are composed by different semiotic modes of communication, such as photographs, drawings, diagrams, graphs, equations and verbal texts. For a reader in enculturation process in the practices of school science it should be provided a way of educating your attention to coordinate reading of these modes. For this reader it should be provided an orientation to help his or her to integrate the information communicated by different modes in the text. To some extent this seems to be done with the indications that refer to a figure, or a details of an equation. However they can choose to follow these guidelines or not. In this investigation we accompanying readers in interaction with a multimodal Physics text. We reproduce a text from a Physics textbook on a computer screen with an eye-tracking system. Eye-tracking system permits to monitorate the reader gaze on the screen. With this system it is possible to rebuild the entire reading path followed by readers in the interaction with the text. The results provided by eye-tracking indicates that the reading paths are very varied. Some readers promote a strong integration of the different modes of communication on the page while others ignore even the integration indications present in the text. Another interesting point that we observed was the predominance of verbal text mode in reading targeting of most of participants. As we accompanied readers in resolving questions, we saw that the non-integration of modes implies difficulties in solving them and that the type of mode, whether more iconic or more schematic, interferes with the attention given to the mode. The schematic modes are considered be more important. Our results about the ways in which readers interact with the texts can offer opportunities for reflection for teachers, teacher trainers and producers of teaching materials that deal with multimodal didactic texts in Physics. It is needed to reflect about the use and the characteristics of the multiple modes commoly used in the teaching Physics.